Comprehensive Treatment of a Rare Case of Complete Primary Pachydermoperiostosis with Large Facial Keloid Scars: A Case Report and Literature Review - Haibo Zhao; Jianglin Zhang; Renliang He; Linlin Bao (Karger Publishers, 2024)
Introduction: Pachydermoperiostosis (PDP), or primary hypertrophic osteoarthropathy, is a rare autosomal dominant disease with primary clinical features of pachydermia (thickening of skin) and periostosis (new bone formation). Keloid scar formation is also rather obscure, and some scientists have claimed that keloid scars contain an excessive amount of fibroblasts compared with normal skin as well as a dense mass of irregularly deposited connective tissues. Case Presentation: A 25-year-old man exhibited extensive skin folding on his face, a gyrus-like scalp, depressed nasolabial folds, and keloids. Symptoms began at 18 years of age, progressing insidiously. Additionally, he experienced clubbing of fingers and toes, joint pain, muscle soreness, and hyperhidrosis. Radiographic examinations revealed thickened bone and cystic regions. Diagnosed with complete primary PDP and facial keloid scars, he underwent skin dermabrasion, biopsies, and a comprehensive treatment involving, botulinum toxin injections, 5-fluorouracil, and a carbon dioxide lattice laser. Conclusion: PDP presents challenges due to its unclear etiology but stabilizes over time in most cases. Comprehensive treatment strategies, including dermabrasion and a combination of intralesional therapies, are effective in managing keloids in PDP patients. This case contributes to the understanding of managing rare diseases and underscores the importance of personalized approaches to improve therapeutic outcomes in patients with complete primary PDP and concurrent keloids.